Pembuatan Bioetanol Dari Fermentasi Nira Aren (Arenga Pinnata) Menggunakan Yeast Saccharomyces Cerevisiae Dengan Pengaruh Variasi Konsentrasi Nutrisi Dan Waktu Fermentasi - Akhir, Yaumil Mutia; Chairul, Chairul; Drastinawati, Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioetanol is one of the environmental friendly biofuel and produced by fermentating it with organic primary resource. Biofuel comes from organic resources called non-fossil energy. One of the most potential feed stock which used as primary resource of making bioetanol is arenga plant. Arenga plant is one of the plant that has sugar content. Microorganism that used for processing the arenga plant into bioetanol was Saccharomyces cerevisiae. The step of this research consist of materials and inoculum preparation, fermentation and also analysis. This research was observed the effect of variation in nutrient concentration and fermentation time. Nutrition used in this research were (NH2)2CO (urea) dan NH4H2PO4 (NPK) where urea was varied into 0,3;0,4;0,5; dan 0,6 g/l whereas NPK was varied into 0,4;0,5;0,6; and 0,7 g/l. Fermentation result were taken after 24, 48, 72 and 96 hours. Optimum urea addition result 0,5 g/l and 0,6 g/l for NPK on 72 hours of fermentation that resulting bioetanol concentration 7% (v/v).Keyword : Arenga plant, bioetanol, fermentation, Saccharomyces cerevisiae.